Bridging climate and social equity: Progressive carbon tax simulations for Belgium - Floore Bursens; Silvia De Poli; Sofia Maier; Gerlinde Verbist (University of Essex, Institute for Social and Economic Research (ISER), 2025)
This paper explores the distributive impact of a hypothetical carbon tax on households' transport and energy consumption in Belgium. It focuses on the welfare effects across population groups and along the income distribution, as well as on the expected budgetary and environmental effects, accounting for consumer responses under a partial equilibrium microsimulation framework. Given the well-known regressive features of consumption taxes in general, and of energy- or carbon-related taxes in particular, this study evaluates various methods for making the carbon tax more progressive and assesses how these methods affect the overall distributional outcomes. We assess both the expected results as well as the feasibility of each of the tax design scenarios, considering the effect on household income and its distribution vis-a-vis the expected reduction in greenhouse gas emissions.
Keywords: H23; Q52; D31; C67; 330; carbon tax; Belgium; Green EUROMOD; regressivity; just transition; price elasticity